2002
DOI: 10.1007/s00415-002-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SCA8 and SCA12 loci in 134 Italian ataxic patients negative for SCA1-3, 6 and 7 CAG expansions

Abstract: Spinocerebellar ataxias (SCA) are a heterogeneous group of neurodegenerative disorders, six of which are caused by expansion of a polyglutamine-coding CAG repeats ( SCA1- 3, 6, 7 and 17). In addition, expansions of a CAG triplet in the 5' region of a gene and a CTG triplet in an antisense RNA have been demonstrated in the SCA12 and SCA8 genes respectively. Our series of 134 ataxic patients (22 familial and 112 sporadic, tested negative for SCAI-3, 6, 7) was investigated for the presence of triplet expansions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The SCA12 mutation was not detected in a patient population that included 180 North American ataxia kindreds of European, Chinese, Japanese, Southeast Asian, East Indian, Middle Eastern, Hispanic, or African-American ethnic descent (Cholfin et al, 2001). The SCA12 mutation has not been found among patients with ataxia of unknown cause in other countries, including the United Kingdom (Worth and Wood, 2001), Italy (Brusco et al, 2002), Portugal or Brazil (Silveira et al, 2002), the Netherlands (van de Warrenburg et al, 2002), Japan (Maruyama et al, 2002;Matsumura et al, 2003), Taiwan, East India (Sinha et al, 2004), Poland (Sułek et al, 2004), or Serbia (Dragasević et al, 2006).…”
Section: Sca12 Distributionmentioning
confidence: 86%
“…The SCA12 mutation was not detected in a patient population that included 180 North American ataxia kindreds of European, Chinese, Japanese, Southeast Asian, East Indian, Middle Eastern, Hispanic, or African-American ethnic descent (Cholfin et al, 2001). The SCA12 mutation has not been found among patients with ataxia of unknown cause in other countries, including the United Kingdom (Worth and Wood, 2001), Italy (Brusco et al, 2002), Portugal or Brazil (Silveira et al, 2002), the Netherlands (van de Warrenburg et al, 2002), Japan (Maruyama et al, 2002;Matsumura et al, 2003), Taiwan, East India (Sinha et al, 2004), Poland (Sułek et al, 2004), or Serbia (Dragasević et al, 2006).…”
Section: Sca12 Distributionmentioning
confidence: 86%
“…However, they did not report either the neuropsychological methods or the criteria for cognitive impairment used in their studies. In three other studies [6,8,19], cognitive functioning has been evaluated using the MMSE, which has been reported to be an insensitive measure of cognitive performances [20]. Zeman et al used, besides MMSE, also the AddenbrookeVs Cognitive Examination, which is, with their own words, insensitive to subtle neuropsychological deficits and executive dysfunction, and neither of the tests did reveal cognitive deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of clinical analyses have demonstrated that SCA8 presents as a very slowly progressive ataxia,13,14 and affected individuals displayed gait, limb ataxia, speech, and oculomotor incoordination. However, there have been several reports of nonataxic symptoms of SCA8 as atypical phenotypes in the past decade.…”
Section: Introductionmentioning
confidence: 99%